Theological Contributions of the Great Commission-Centred Church in a Multicultural Society - Susanto Susanto; Tonny Andrian Stefanus; Maria Titik Windarti (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2025)
The church has the main mandate to carry out the Great Commission as written in Matthew 28:18-20. In the context of an increasingly complex multicultural society in the digital era and society 5.0, the church is faced with the challenge of delivering the gospel in a relevant manner without losing its theological essence. This research aims to examine the theological contribution of the church in carrying out the Great Commission in a multicultural society and formulate effective strategies in evangelism. Using a qualitative method based on literature review, this research analyses literature from various sources of theology, sociology of religion, and multiculturalism studies. The results show that the church has an important role in building social harmony through interfaith dialogue, multicultural education, and inclusive and contextual evangelism strategies. Churches that understand local cultures can bridge social and religious differences without losing Christian values. In addition, the utilisation of digital technology in church mission strategies allows for greater reach in the spread of the gospel. However, challenges remain, including theological differences, resistance to evangelism, as well as limited church resources in social ministry. Therefore, a collaborative approach with various communities becomes a strategic solution to strengthen the impact of the church's ministry. This research confirms that the church needs to continue developing mission methods that are relevant to the times, while remaining true to its theological principles. By actively engaging in social ministry and interfaith dialogue, the church can become an agent of social transformation that brings peace and prosperity to a multicultural society.